THE ABILITY OF HEALTH ORGANIZATIONS TO CHANGE - WHY DO CHANGE NEED A PROCESS AND PROJECT APPROACH? - Jasinska, Joanna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2020)
The aim of the article is an attempt to identify the relationship between various disciplines of management sciences (change management, process management, project management) and to refer to the problem of their application in healthcare organizations. This seems to be a serious problem in the context of the inevitability of changes in medical organizations, especially in the face of an ongoing pandemic (organizational changes over a relatively short period of time). In addition, the ever-increasing complexity of healthcare organization and at the same time the pace of technological innovation in medicine. The article is a review it integrates and interprets the current state of knowledge in the field of change management, process management and project management. It indicates the need to integrate various management sub-disciplines. It was mainly developed using critical literature analysis. Healthcare organizations, especially during the global COWID-19 pandemic are undergoing a process of rapid organizational change. It is important to understand these changes not only theoretically but as a set of necessary skills. All this to efficiently and effectively implement the paradigm of managing modern health organizations. Knowledge and experience in change management as well as knowledge of the principles of project and process management seem to be necessary for the proper implementation of effective and efficient management of health care institutions. It is worth emphasizing that currently the interest in project management and change management is usually focused on ensuring the effectiveness of changes. Therefore it becomes necessary to know the subcategories of management, such as: project management, process management, human potential management, quality management.